The Role of Population Growth and Political Instability in Youth Unemployment in Pakistan (Journal of Asian Development Studies, 2025)
Youth unemployment is a critical challenge for Pakistan, with severe long‑run effects for economic growth and social stability. This research analyzes the long-run impact of youth unemployment, GDP growth, population growth, and political instability on Pakistan’s economy. In this study, we perform multiple diagnostic tests, including unit root tests, multicollinearity, normality, heteroscedasticity, specification bias, and autocorrelation, to assess the validity of the model. The Autoregressive Distributed Lag (ARDL) method is used to examine both the long- and short-run associations among variables. Findings of this research indicate that, as economic growth is inversely correlated with youth joblessness, sustained economic growth reduces youth unemployment in Pakistan; however, political instability & population growth show a direct and meaningful association with youth unemployment, imposing rising constraints on economic growth. This research provides key policy suggestions on the influence of economic growth & political volatility on the country's overall economic efficiency.